The curse of the bologna sandwich - Trine, Greg.; Montijo, Rhode (New York : Henry Holt, 2006)
After graduating from the superhero academy, Melvin Beederman heads for Los Angeles, where he unexpectedly teams up with Candace Brinkwater, school play actress, to nab the evil McNasty Brothers.
Keywords: Heroes -- Fiction; Humorous stories; Los Angeles (Calif.) -- Fiction